12z+7=67+9z

Simple and best practice solution for 12z+7=67+9z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12z+7=67+9z equation:


Simplifying
12z + 7 = 67 + 9z

Reorder the terms:
7 + 12z = 67 + 9z

Solving
7 + 12z = 67 + 9z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-9z' to each side of the equation.
7 + 12z + -9z = 67 + 9z + -9z

Combine like terms: 12z + -9z = 3z
7 + 3z = 67 + 9z + -9z

Combine like terms: 9z + -9z = 0
7 + 3z = 67 + 0
7 + 3z = 67

Add '-7' to each side of the equation.
7 + -7 + 3z = 67 + -7

Combine like terms: 7 + -7 = 0
0 + 3z = 67 + -7
3z = 67 + -7

Combine like terms: 67 + -7 = 60
3z = 60

Divide each side by '3'.
z = 20

Simplifying
z = 20

See similar equations:

| 4(h-7)+4=-8 | | 2(c+10)-9=7 | | 5t-7+9t=4t-33 | | 6m-2=19-m | | 5(h-1)+6=-9 | | 2(w+5)-1=5 | | -4(s-6)-3=9 | | -(b-9)+2=3 | | 3u+4=2u-9 | | 20x+15=30x+10 | | 4(d+3)+2=10 | | 3(d-12)=d+24 | | 9b+10=1 | | 2p+8=6 | | 3x+26=x+4 | | 20+8=6 | | 2x-4x^2= | | 16-3t=-7t | | 18-5(x+1)=3(x-1) | | 10g-47-4g=16+3g | | 8x^3-6x+1=0 | | 22-4x=2x-4 | | w-5+3w=6w-1 | | 10c+5=4c-1 | | 3x+3=4x-6 | | 7(x-10)=21 | | 14*(2x+2)=1716+6*(x+2) | | x^2+6x+8=e^2 | | z^2+iz=0 | | 3.3x=6.5(10x+4) | | ln(2x^2+7x-4)=2+ln(x^2+x-12) | | -1+(2t+3)+2(t-3)= |

Equations solver categories